Where to Locate Innovative Activities in Global Value Chains Does Co-location Matter? - Belderbos, Rene (OECD Science, Technology and Industry Policy Papers, 2016)
With the emergence of global value chains (GVCs), production processes are increasingly fragmented and dispersed across different countries. Although many MNEs still exhibit an important 'home bias' in their global innovation activities, a growing number of firms have offshored R&D and innovative activities to foreign locations. Is the more recent offshoring of R&D and innovation linked to the prior waves of manufacturing offshoring? The fear in OECD economies is that because of co-location effects between production and innovative activities, the loss of certain manufacturing/assembly activities may result in a loss of innovative capabilities (R&D, design, etc.) in the longer-term. The offshoring of R&D and innovation within GVCs poses new challenges to economic policy in OECD and emerging economies. For example, how can countries attract inward R&D investments by foreign MNEs? Should outward R&D investments by MNEs be a concern for the countries in which the MNEs are headquartered?